2022
DOI: 10.1021/acsestengg.1c00464
|View full text |Cite
|
Sign up to set email alerts
|

Nonradical Activation of Peroxydisulfate with In Situ Generated Amorphous MnO2 in an Electro-Permanganate Process: Involvement of Singlet Oxygen, Electron Transfer, and Mn(III)aq

Abstract: A novel water treatment process based on a combination of electrolysis (E) with permanganate (PM) and peroxydisulfate (PDS) was systematically investigated. The combination exhibited significant synergy in degrading refractory organics such as diclofenac (DCF), carbamazepine, and nitrobenzene. In comparison to E-PDS (20.45%, 12.448 kWh m–3) and E-PM (36.36%, 5.200 kWh m–3) processes, the E-PM-PDS process could mineralize 70.45% DCF within 180 min with the lowest specific energy consumption (1.007 kWh m–3). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…MnO 2 colloids formed from Mn­(VII) decomposition generally exhibit excellent reactivity in removing contaminates through oxidation and/or catalytic processes. , Figure S13 unravels that phenol degradation by ectopically prepared MnO 2 colloids cannot be accelerated by HCO 3 – , suggesting that the enhanced removal of phenol is not associated with an increase in the oxidation ability of MnO 2 . Moreover, a previous study demonstrated the limited role of MnO 2 in phenol removal at pH 3.0–8.0 .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…MnO 2 colloids formed from Mn­(VII) decomposition generally exhibit excellent reactivity in removing contaminates through oxidation and/or catalytic processes. , Figure S13 unravels that phenol degradation by ectopically prepared MnO 2 colloids cannot be accelerated by HCO 3 – , suggesting that the enhanced removal of phenol is not associated with an increase in the oxidation ability of MnO 2 . Moreover, a previous study demonstrated the limited role of MnO 2 in phenol removal at pH 3.0–8.0 .…”
Section: Resultsmentioning
confidence: 94%
“…The renascent MnO 2 colloids with abundant surface hydroxyl groups and large surface areas can drive the removal of micropollutants by Mn(VII) via oxidation, catalysis, and coagulation processes. 11,12 This suggests that colloidal MnO 2 is a paramount intermediate for regulating the overall decontamination performance of Mn(VII). Many studies have reported that solution chemistry, including reductive agent dosage and concomitant ions, strongly impacts the Mn(VII) conversion product MnO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations